Apathy as a Risky Neuropsychiatric Syndrome of Progression From Normal Aging to Mild Cognitive Impairment and Dementia: A Systematic Review and Meta-Analysis - Fan, Zili; Wang, Luchun; Zhang, Haifeng; Lv, Xiaozhen; Tu, Lihui; Zhang, Ming; Zhang, Ying; Yan, Caihua; Yu, Xin; Wang, Huali (Frontiers in Psychiatry, 2021)
Background: Apathy has been suggested as a potential predictor of mild cognitive impairment (MCI) progression to dementia. Whether it might predict the transition from normal cognitive function to cognitive impairment has been less studied. The current study aimed to provide a comprehensive summary of the evidence on the association between apathy and the transition from normal cognitive function to cognitive impairment. Methods: We searched the PubMed, Embase, and Web of Science databases for longitudinal prospective cohort studies that evaluated apathy at baseline in the cognitively normal population and had cognitive impairment as the outcome. Random effects models were used, and heterogeneity was explored with stratification. The stability of the synthesized result was indicated using sensitivity analysis by excluding one study each time and recalculating the overall effect. Results: Ten studies comprising 26,195 participants were included. Apathy status was available for 22,101 participants. Apathy was present in 1,803 of 22,101 participants (8.16%). Follow-up ranged from 1 to 13 years. The combined odds ratio (OR) of cognitive impairment for patients with apathy was 2.07 (95% CI: 1.43-2.99; I2= 86%), and the combined hazard ratio was 2.70 (95% CI: 1.38-5.27; I2 = 94%). The OR meta-analyses for different conversion outcomes were MCI (OR=3.38, 95% CI: 1.57-7.28; I2 =71%), cognitive decline (OR=1.27, 95% CI: 0.81-2.00; I2 =64%) and dementia (OR=2.12, 95% CI: 1.32-3.41; I2 =86%). Subgroup analysis suggested that the association between apathy and cognitive impairment changed with age, depression adjustments, apathy measurement, and follow-up time. Conclusions: Apathy was associated with a greater than 2-fold increased risk of progression to cognitive impairment in the cognitively normal population. Future interventions targeting apathy management in the general population may reduce the risk of cognitive impairment.